Features of Functioning of Bacchic Vocabulary in Novel of D. S. Merezhkovsky “Peter and Alexei” - O. A. Dimitrieva (Научный диалог, 2022)
The features of the situation of wine drinking, its individual author’s interpretation in D. S. Merezhkovsky’s novel “Peter and Alexei” are considered. The relevance of the study is connected, firstly, with its inclusion in the circle of studies related to the study of the author’s idiostyle, and secondly, with determining the influence of the views of the author-symbolist on the representation of the details of everyday life, in particular the situation of drinking wine. The material for the research was a selection of contexts containing Bacchic vocabulary. The novelty of the study is seen in the fact that this novel is considered from the point of view of the representation of everyday values in the context of a historiosophical novel. While traditionally the novel is defined as a symbolist one, its importance in expressing the religious and philosophical views of the author is emphasized. It was revealed that the inclusion of words denoting the name of the dishes (chan, ushat, flyaga, etc.) in the picture of Peter’s “most drunken cathedrals” gives wine-drinking features of inclusiveness and scale. Attention is paid to the symbolic reading of wine, and it is also noted that the sacred and the profane are in constant relationship and often have a Bacchic interpretation. It is indicated that vocabulary with the semantics of death is introduced into the wine-drinking scenes, which sets a symbolic interpretation and explicates the author's assessment.